Poverty Reduction Strategies Based On The Development Of Small Businesses - Aripov, Oybek Abdullaevich; Ismailov, Muhammadali (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
Poverty remains one of the most persistent global challenges of the 21st century, affecting millions of individuals across both developed and developing nations. As governments, economists, and international organizations strive to devise sustainable solutions, small business development has emerged as one of the most effective and inclusive strategies for poverty reduction. This article explores how the growth and empowerment of small businesses can serve as a powerful catalyst for alleviating poverty. It examines the relationship between entrepreneurship, employment creation, innovation, and local economic development, emphasizing the importance of access to finance, capacity building, and government support. The discussion also highlights the role of technology, education, and gender inclusion in empowering marginalized groups. By analyzing successful models from various countries, the paper underscores how small business development contributes not only to poverty reduction but also to long-term socio-economic stability.